METABOLIT SEKUNDER DARI FRAKSI AKTIF AKAR PANDAN (Pandanus amaryllifolius roxb.) YANG BERSIFAT ANTIFEEDANT TERHADAP Epilachna sparsa (SECONDARY METABOLITES OF THE ACTIVE FRACTION OF PANDAN ROOT (Pandanus amaryllifolius roxb.) AS ANTIFEEDANT AGAINST Epilachna sparsa) - Ari Widiyantoro; Harlia Harlia; Annisa Dyah Astari Putri (Tanjungpura University, 2023)
Pandan wangi (Pandanus amaryllifolius Roxb.) contains flavonoids, terpenoids, steroids, saponins, alkaloids and tannins which can be used as antifeedant compounds. This study aims to determine the antifeedant activity and to identify of secondary metabolites from pandan roots extract against Epilachna sparsa. The antifeedant activity test was carried out on the methanol extract and the partition yeild fraction. The research was carried out by maceration of pandan root which had been mashed into powder with methanol solution to obtain a methanol extract of 86.51 g. The extract was then separated by partitioning to obtain methanol fraction, ethyl acetate fraction, dichloromethane fraction and n-hexane fraction. The methanol extract and fraction from partition results were then tested for antifeedant activity against Epilachna sparsa. The results showed that at a concentration of 6% the methanol extract had an antifeedant activity of 59.37 ± 2.11 % against Epilachna sparsa. The fractions resulting from the partition included methanol, ethyl acetate, dichloromethane and n-hexane fractions at a concentration of 6% respectively showing antifeedant activity of 81.25 ± 3.56 %; 75.00 ± 2.99 %; 37.50 ± 3.77 % and 21.18 ±1.23 %. Based on the antifeedant activity test results, the methanol fraction showed the best activity. Furthermore, the methanol fraction was separated and purified by chromatographic techniques. The isolate obtained was 53.11 mg in the form of white needle crystals and had a melting point of 135-138oC. The isolate based on the phytochemical test showed positive for flavonoid